PHYSICOCHEMICAL PROPERTIES ANALYSIS OF LOCAL CERAMICS WITH ACTIVATED CARBON ADDITIVE BASED ON RUBBER FRUIT SHELLS AS THERMAL INSULATORS - Kurniawan, Chandra; Yuliza, Elfi; Irkhos, Irkhos; Fitriani, Dyah (Universitas Mataram, 2023)
Many building materials that function as insulators to maintain indoor temperature stability during hot weather have been developed. One of them is porous ceramics applied to building walls as heat absorbers. Research related to the manufacture of porous ceramics began to emerge to find the optimal composition when applied as an insulator that can absorb heat well. In general, porous ceramics use activated carbon as a pore agent. Activated carbon can be obtained by carbonating agricultural wastes such as coconut shells, hazelnut shells, rubber fruit shells, rice husks, and cocoa shells. Research continues to develop in finding the best-activated carbon base material according to the required material characteristics. Researchers will take advantage of the abundant potential of local natural resources. The method used to make porous ceramics is to mix clay and activated carbon with a clay-carbon composition ratio of 100:0, 90:10, 80:20, 70:30, 60:40, and 50:50. The sample is made by mixing the two materials and then printed by dry pressing method with a load of 5 tons held for 10 minutes. After the sample is dried at room temperature, it is sintered at 900oC with a holding time of 3 hours. Next, the sample is characterized by determining density, porosity, and water absorption and then tested for thermal properties. After that, the surface morphology and elements in the sample are seen. The optimum composition of clay-carbon mixture is 70:30 grams.Â Ceramics using activated carbon from rubber fruit shells are suitable as building construction materials as heat insulators because they can absorb heat up to 500oC.